2006
DOI: 10.1177/0003319706293119
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Smoking Cessation on Hemodynamics and Arterial Compliance

Abstract: Cigarette smoking is associated with consistent changes in small arteries and arterioles. Recently, arterial compliance was determined in smokers; however, the effect of smoking cessation on arterial compliance has not yet been investigated. The objective of the study was to assess how smoking cessation, achieved with use of behavioral and pharmacologic therapy, influences vascular compliance and arterial stiffness in smokers. In an open-label study, 60 habitual smokers were treated for 2 months with buproprio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 29 publications
(31 reference statements)
4
20
0
3
Order By: Relevance
“…However, it remains controversial whether arterial stiffness improves after smoking cessation; some studies show rapid improvement in AIx after smoking cessation, 42,58,59 whereas cfPWV did not improve after 6 months, 59 and another study showed no improvement in distensibility after 2 years. 59,60 A crosssectional study of middle-aged hypertensive patients found that AIx, cfPWV and T r (transit time) returned to baseline levels only after 10 years of smoking cessation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it remains controversial whether arterial stiffness improves after smoking cessation; some studies show rapid improvement in AIx after smoking cessation, 42,58,59 whereas cfPWV did not improve after 6 months, 59 and another study showed no improvement in distensibility after 2 years. 59,60 A crosssectional study of middle-aged hypertensive patients found that AIx, cfPWV and T r (transit time) returned to baseline levels only after 10 years of smoking cessation.…”
Section: Discussionmentioning
confidence: 99%
“…Oren et al 58 and Polonia et al 59 observed a decrease in AIx after 6 months of smoking cessation; continuing smokers showed no such change. 58,59 Rehill et al 42 Berlin et al 25 Healthy male CS Before vs. after smoking brPWV Acute smoking: increase by 28% 15 min after smoking, return to baseline at 30 min…”
Section: Smoking Cessationmentioning
confidence: 95%
“…Even in light smokers who do not smoke more than 20 cigarettes per day can be detected changes in arterial elasticity 7 . Recent research in this fi eld suggests that vascular function is improved even after six months after quitting smoking 8 . Rehill et all claim that positive changes in arterial elasticity can be seen even after 4 weeks of cigarette abstinence 9 .…”
Section: Discussionmentioning
confidence: 99%
“…22 Smoking cessation reverses some of these deleterious effects (eg, arterial stiffness and anklebrachial pressure index). 23,24 Smoking acts synergistically with other vascular risk factors (such as hypertension, DM, and hyperlipidemia) to increase vascular morbidity and mortality. 25 It was demonstrated that smoking is associated with a variable magnitude of cardiovascular risk for different vascular diseases; the risk is highest for PAD and abdominal aortic aneurysms (AAAs) and lowest for cerebrovascular diseases.…”
Section: Smokingmentioning
confidence: 99%